(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation.Technology is increasingly shaping the design and delivery of English language programs globally.Language teachers must integrate technology and assist students in using resources like media and the internet to enhance their learning of all four skills. Technology creates both obstacles and opportunity for instructors and students. This article examines the impact of technology on language education and the opportunities it provides for instructors and learners to promote technology mediated teaching and learning.